Causas in Partibus Cognoscendas: An Edition of a Vatican Document and Its Possibilities for Future Research on Papal Judges Delegate in Late Medieval Castile - Benítez-Inglott y Ballesteros, Eduardo (Anthologica Annua, 2023)
This article offers a commentary, edition, transcription, and translation of a papal letter issued during Martin V’s pontificate to King Juan II of Castile: Per Litteras. Largely overlooked until now, Per Litteras is a highly interesting source because it leads us to start considering the phenomenon of papal judges delegate in the Crown of Castile in the Late Middle Ages. This paper begins by analysing Per Litteras’ contents. Given that the letter is undated, we will propose a date of production. We will then proceed to place it into the broader context of diplomatic exchanges between the Holy See and the Crown of Castile. Finally, we discuss how the document may help us understand papal delegated jurisdiction in late medieval Castile.